High ratio of monocytes to high-density lipoprotein is associated with hemorrhagic transformation in acute ischemic stroke patients on intravenous thrombolysis - Xia, Lingfan; Xu, Tong; Zhan, Zhenxiang; Wu, Yucong; Xu, Ye; Cao, Yungang; Han, Zhao (Frontiers in Aging Neuroscience, 2022)
Background: Hemorrhagic transformation (HT) is a frequent, serious complication in acute ischemic stroke patients on intravenous thrombolysis. Here we investigated whether risk of HT is associated with the ratio of monocyte count to high-density lipoprotein level (MHR). Methods: Medical records were retrospectively examined for consecutive patients with acute ischemic stroke who received thrombolytic therapy. HT was diagnosed by computed tomography at 24-36 h after therapy. Potential association between MHR and HT was examined using logistic regression. Results: A total of 340 patients were analyzed, and their median MHR was 0.44 (0.31-0.59). MHR was higher in the 51 patients (15.0%) with HT than in those who did not suffer HT (0.53 vs 0.42, P = 0.001). Multivariate logistic regression showed that, after adjusting for potential confounders, MHR was an independent risk factor for HT (OR 4.45, 95% CI 1.06 to 18.64, P = 0.041). Risk of HT was significantly higher among patients whose MHR fell in the fourth quartile (> 0.53) than among those with MHR in the first quartile (< 0.31; OR 3.46, 95% CI 1.13 to 10.57, P = 0.030). Conclusions: High MHR may be independently associated with higher risk of HT in patients with acute ischemic stroke on intravenous thrombolysis.